Emergency preparedness amongst Emergency Response Team in managing accidents at the workplace involving hazardous materials vis-À-vis the Occupational Safety and Health Act 1994 - Azuddin, Bahari, Lt Kol (B); Hanum, Hassan (Universiti Malaysia Perlis, 2010)
Hazardous materials are chemical substances, which if released or misused can pose a threat to the environment or health. Recently, various type of crisis or emergency due to hazardous materials handling had occurred at the workplace due to human negligence and weaknesses which causes loss of lives and property. Accidents at the workplace involving hazardous materials are most often due to release of chemical substances in plants. During an emergency, individuals may panic or overreact. As a consequence early actions have to be taken to address the crisis. Disaster area needs to be secured in order to prevent unauthorized access and to protect the installation and equipment. These initial tasks can be undertaken by Emergency Response Teams (ERT). The ERT is the first responder in emergencies while waiting for assistance from the relevant authorities such as the Fire and Rescue Department to deal with the crisis at hand. In addition, to ensure ERT and the management is on alert for emergency situations at all times, the ERT in general and the company or business entity in particular ought to be assessed, at least annually with mock drills and competence evacuations. Against this background, should a major catastrophe involving hazardous materials strike the workplace will the ERT be ready to manage the crisis? Is their emergency preparedness machinery geared up? What part can the ERT play to contributes in the management of this crisis? This paper endeavor to highlight the role of the ERT in managing accidents at the workplace involving hazardous material.